Pengaruh Kemampuan Individu Dan Dukungan Organisasi Terhadap Kompetensi Kerja Karyawan - Wahyu Cahyono; Hadi Sunaryo; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2020)
ABSTRACTThis research purpose to determine: 1) Description of individual ability, organizational support and employee work competence at PT Bank X Malang, 2) The effect of individual ability and organizational support to employee work competence at PT Bank X Malang, 3) The effect of organizational support to employee work competence at PT Bank X Malang, 4) The effect of individual ability to employee work competence at PT Bank X Malang.The method used in this research is quantitative with a descriptive approach and conducted at PT Bank X Malang with total population 40 employees. Data collection technique used questionnaire with likert scale measurement. Data analysis technique used is validity, reliability, normality, multiple linear regression analysis, multicollinearity, heteroscedasticity, hypothesis F, hypothesis t, and coefficient of determination.The result of this research indicate that: 1) individual ability and organizational support does a significant effect to employee work competence at PT Bank X Malang, 2) Individual ability does a significant effect to employee work competence at PT Bank X Malang, 3) Organizational support does not a significant effect to employee work competence at PT Bank X Malang. Keywords : employee work competence, organizational support, individual ability